Síntesis y caracterización de complejos de cromo(III) y hierro(III) que contienen ligandos derivados de azoles (2017)
For the development of this work three Cr(III) and Fe(III) complexes were synthesized with the bis(3,5-dimethyl-1-pyrazolyl)-methane ligand. Also the synthesis of the sulfonates and nitro derives of the aforementioned ligand where achieved. The ligands were characterized by means of the melting point, 1H-NMR, 13C-NMR, HSQC, UV-Vis and Raman spectroscopy. For the case of the complexes, the characterization was performed by the melting point, elemental analysis, Raman spectroscopy, thermogravimetric analysis, mass spectrometry (GC-EI and HPLA-ESI) and UV-Vis spectroscopy. The relation between ligand and metal for complex 2 and 3 is probably 1:1. Geometrical structure of this complex is proposed as octahedral.